A Study on Family Planning Methods Among HIV Sero Discordant Couples in Karnataka - Sunil Kumar; Amruth Sagara; Waseem Anjum; Vidya (Medsci Publications, 2016)
Introduction: India has third largest number of people living with HIV/AIDS in the world. Sero-discordance in couples refers to two people (One HIV positive and other negative) who are in ongoing sexual relationship in which both partners have tested for HIV and there has been full disclosure of HIV status. This study aims to understand planning methods and adherence to ART treatment among HIV sero-discordant couples in Karnataka. Methods: A cross sectional study was conducted in Karnataka from Apr to September 2015 .A total of 314 sero-discordant couples enrolled in PLHIV Networks for HIV care and support services in 4 sites of Karnataka were selected for the study . Results: Majority (79%) of sero-discordant couples have adopted sterilization method of contraception. The condom usage (12%) and copper-T(2%) methods were pretty low. Adherence to ART (≥ 95%) among sero-discordant couples was high at 94.6%. PLHIV with a spouse having higher educational status were better adher- ing to ART on comparison with spouse of lower educational sta- tus. This difference was statistically significant (P<0.01). Conclusion: The study shows that the HIV sero-discordant couples are using sterilization methods more in comparison to other family planning methods and are highly adherent to ART.